Forest family : Australian culture, art, and trees - Ryan, John (Poet) (Critical Plant Studies, 2018)
Forest Family highlights the importance of the old-growth forests of Southwest Australia to art, culture, history, politics, and community identity. The volume weaves together the natural and cultural histories of Southwest eucalypt forests, spanning pre-settlement, colonial, and contemporary periods. The contributors critique a range of content including historical documents, music, novels, paintings, performances, photography, poetry, and sculpture representing ancient Australian forests. Forest Family centers on the relationship between old-growth nature and human culture through the narrative strand of the Giblett family of Western Australia and the forests in which they settled during the nineteenth century. The volume will be of interest to general readers of environmental history, as well as scholars in critical plant studies and the environmental humanities.